Oxigenoterapia en el tratamiento paleativo del asma bronquial en el adulto mayor atendido en el Centro Gerontológico del Cantón Babahoyo Provincia Los Ríos en el periodo octubre 2019 - marzo 2020. - Escalante Baño, Estibaliz Cecilia (2020)
In this research study we will talk about oxygen therapy as a palliative treatment of bronchial asthma in the elderly who is treated in the gerontological center of the Babahoyo canton, Province of the Rivers in the period of October 2019 - March 2020. The general objective of this project is to determine the usefulness of oxygen therapy as a palliative treatment of bronchial asthma in the elderly, for which we will build on the specific objectives which will help us determine the usefulness of such treatment in this disease. Because bronchial asthma in adults has been one of the first causes of mortality with a prevalence of 3-5% with variations that can range between 2-12%. Taking into account that the majority of these patients have presented this disease from childhood to old age, the main causes of bronchial asthma being allergen, environmental and, above all, the lifestyle that most of these patients have led. Oxygen therapy is not the main treatment in this pathology, but nevertheless this treatment Will help older adults to improve their quality of life and to control asthmatic crises and possible complications that may occur. Through the access to the patients' medical history, a result of 25 older adults with bronchial asthma was found, presenting symptoms such as dyspnea, wheezing and roncus, which confirmed that they had such pathology. It was found that oxygen therapy for older adults helped to improve their symptoms and asthmatic crises, which in turn gave them a better quality of life.